A Study on the satisfaction of Chinese bed and breakfast based on big data reviews - Xu Qingyong; Lu Zixian; Li Yujing; Ye Xin (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Purpose B&B stays have enjoyed popularity in China over recent decades. Online reviews can truly and objectively reflect consumers' satisfaction. Using the network text analysis method, this study analyses the overall satisfaction, the trend of satisfaction, and the main factors affecting consumers' satisfaction by taking the TOP50 online reviews of China B&B as the sample. The results show that the overall satisfaction degree of the Top 50 of China's B&B List is relatively high, and it has continuously improved in the past three years. But there are still some negative evaluations. The core competitiveness is service, focusing on personalized needs and humanistic care, while the weakness in the room hardware is also important to improve satisfaction. The personalized service, infrastructure, the service process, and internal & external environment should be improved to improve consumers' satisfaction with the homestay. The research attempts to provide theoretical and practical references for improving service quality.